Upaya Meningkatkan Hasil Belajar Siswa dengan Menggunakan Strategi Omaggio pada Mata Pelajaran Bahasa Indonesia Tingkat Madrasah Ibtidaiyah - Darmawan, Iwan; Nurteti, Lilis; Meidawaty, Sri (Bestari, 2019)
This research is motivated by the low learning outcomes of students of grade V Madrasah Ibtidaiyah Thoriqun Najah on learning Indonesian language subject matter elements. In an effort to improve student learning outcomes, researchers used the "Omaggio strategy". Classroom management can be done by approach through variations of learning strategies. Learning strategy has a very big role in the learning process. Such learning strategies include "Omaggio strategy". The objectives of this research are: 1) To improve the ability of teachers in preparing the Lesson Plans on Indonesian subjects listening to the subject matter elements by using "Omaggio strategy", 2) To improve the ability of teachers in the process of learning the language Indonesia aspects of listening to the subject elements of the story by using "Omaggio strategy", 3) To improve student learning outcomes on the subjects of Indonesian language aspects of listening to the subject elements of the story by using "Omaggio strategy". The method used is Classroom Action Research Method model Kurt Lewin. Data collection techniques used are observation, test or assessment techniques and description analysis techniques. After conducting the research, the final result data can be obtained as follows: 1) the ability of teachers in designing the learning aspect listening Indonesian language with an average value of 96.15. 2) the skills of teachers in the implementation of learning Indonesian listening aspects with an average value of 97.22. 3) Students' learning outcomes on Indonesian subjects listened to an average score of 82.19. This proves that "Omaggio strategy" can improve student learning outcomes in Indonesian subjects listening aspect of the story elements in class V Madrasah Ibtidaiyah Thoriqun Najah Sukadana District Ciamis Regency. The results of the analysis show that the proposed hypothesis is acceptable